Microstructural study of Al-Si-Mg alloy reinforced with stainless steel wires composite via casting technique - Mazlee, Mohd Noor; Shamsul Baharin, Jamaludin; Kamarudin, Hussin (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/index.php